Interactive Animated Design Introduction of Indonesian State Map in Basic School 15 Tibang Banda Aceh Based on Multimedia - Fathiah, Fathiah; Fakhrurrazi, Fakhrurrazi (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
The use of technology will automatically provides convenience in the delivery of information. In this research, the utilization of technology can be done by using animation to help and increase the interest of the students in following the learning process to make it more efficient. This is done because some of the material that is studied sometimes seems boring for the students especially in studying the learning materials of Geography science, even today the students of 15 Tibang Banda Aceh are less interested in studying the map of Indonesia, because the current teacher only gives explanation through the books so as not Interesting and boring, in addition to lack of means and other information media such as pictures and encyclopedias provided at the school. From this problem, the authors conducted research on interactive animation design of the introduction of state map of Indonesia at State Elementary School 15 Tibang Banda Aceh based multimedia. Software used in this research is Adobe Professional CS6, Adobe Photoshop, and Wondershare Filmora. The method used in this study is a qualitative method which is a research method that is more focused with the situation or the phenomena studied. Keywords : map of Indonesia, interactive animation, learning